Long cyclic stability of acidic aqueous zinc-ion batteries achieved by atomic layer deposition: the effect of the induced orientation growth of the Zn anode. Issue 28 (9th July 2021) - Zeng, Zhisen; Zeng, Yuehong; Sun, Lingna; Mi, Hongwei; Deng, Libo; Zhang, Peixin; Ren, Xiangzhong; Li, Yongliang
Abstract : The relationships between the Zn orientation textures and ultrathin mental oxide layers deposited by atomic layer deposition were exposed in Zn-ion batteries. Abstract : Aqueous Zn-ion batteries with economical ZnSO4 solution as the electrolyte suffer from a tremendous tendency of dendrite formation under mildly acidic conditions; moreover, utilization of Zn(CF3 SO3 )2 delivers superior performance, but is expensive. Herein, we optimize the ZnSO4 electrolyte by inducing 50 μL of 10 M sulfuric acid in 10 mL electrolyte, which can achieve long cycle life (1000 h at 0.1 mA cm −2, 300 h at 1 mA cm −2 and 250 h at 10 mA cm −2 ) when the Zn foil is protected by three metallic oxides deposited by atomic layer deposition (ALD). The nucleation behaviour of the (002) facet has proved to play a critical role in the reversible lifespan. The Al2 O3 layer would restrict the stripping procedure, leading to the highest overpotential, while the TiO2 layer and Fe2 O3 layer tended to strip all orientations but the (002) facet. Al2 O3 @Zn demonstrated a preference for a compact hillock-like (101) orientation texture in the deposition procedure, while TiO2 @Zn and Fe2 O3 @Zn were favourable to obtain a smooth terrace texture. Additionally, symmetric cells with Fe2 O3 @Zn expressed the lowest overpotential (31.64 mV) and minimal voltage hysteresis (23.6 mV) at 1 mA cm −2 . A Zn-MnO2 battery with Fe2 O3 @Zn also displayed superior capacity, which could reach 280 mA h g −1 at a current density of 1 A g −1 . The diffusion coefficient of Zn 2+ discloses that among the three ALD layers, full cells with Fe2 O3 @Zn are the most favourable for diffusion of Zn 2+ in acidic electrolyte.